2013
DOI: 10.1074/jbc.m112.423053
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acid Adenine Dinucleotide Phosphate (NAADP) Activates Global and Heterogeneous Local Ca2+ Signals from NAADP- and Ryanodine Receptor-gated Ca2+ Stores in Pulmonary Arterial Myocytes

Abstract: Background: NAADP activates Ca 2ϩ release from endolysosomal organelles. Results: NAADP activates two-pore channels in pulmonary arterial smooth muscle cells to elicit global and heterogeneous subcellular Ca 2ϩ signals from NAADP-and ryanodine-sensitive Ca 2ϩ stores, which contribute to the agonist-induced response. Conclusion: NAADP mediates complex Ca 2ϩ interactions between endolysosomes and the sarcoplasmic reticulum to regulate vascular reactivity and other cellular functions. Significance: The results im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 63 publications
3
41
0
Order By: Relevance
“…It has been suggested that a reduction of b-NAD 1 :b-NADH ratio during hypoxia stimulates cyclase activity and inhibits hydrolase activity of CD38, leading to the accumulation of cADPR to activate RyR-gated Ca 21 release for the sustained HPV (22,27). This hypothesis has yet to be verified because a recent study failed to observe the contribution of CD38 to HPV in isolated rat PAs without precontracted with a vasoactive agonist (28) (13,29). Apart from the abovementioned studies, there is no related information on any other vasoactive agonist and on the mechanism underlying agonist-induced activation of CD38 in PASMCs.…”
Section: Clinical Relevancementioning
confidence: 69%
See 4 more Smart Citations
“…It has been suggested that a reduction of b-NAD 1 :b-NADH ratio during hypoxia stimulates cyclase activity and inhibits hydrolase activity of CD38, leading to the accumulation of cADPR to activate RyR-gated Ca 21 release for the sustained HPV (22,27). This hypothesis has yet to be verified because a recent study failed to observe the contribution of CD38 to HPV in isolated rat PAs without precontracted with a vasoactive agonist (28) (13,29). Apart from the abovementioned studies, there is no related information on any other vasoactive agonist and on the mechanism underlying agonist-induced activation of CD38 in PASMCs.…”
Section: Clinical Relevancementioning
confidence: 69%
“…Previous studies from our and other laboratories have identified the expression of RyR and TPC subtypes and have characterized Ca 21 release signals from RyR-gated Ca 21 stores (23)(24)(25) and NAADP-gated acidic endo-lysosomes in rat PASMCs (13,21). Hence, all the components of the CD38-dependent Ca 21 pathways are operational in PASMCs.…”
Section: Clinical Relevancementioning
confidence: 98%
See 3 more Smart Citations